Tracking the natural evolution of bearing spall size using cyclic natural frequency perturbations in vibration signals. (April 2021) - Zhang, Hengcheng; Borghesani, Pietro; Smith, Wade A.; Randall, Robert B.; Shahriar, Md Rifat; Peng, Zhongxiao
Highlights: The duration of natural frequency perturbations is found informative of spall size. The WVS is utilized to identify the cyclic behaviour of natural frequencies. This approach overcomes the limitation of entry/exit-based methods for natural spalls. The new approach is validated and compared with existing methods in three tests. Abstract: Spalling caused by fatigue is the most common reason for rolling element bearing failure, and spall size can be a good indicator to predict the remaining useful life of the bearing. Previous studies reported that, in the acceleration signal, a low-frequency step response is caused by de-stressing or re-stressing of the rolling element during its entry into and exit from the spall zone, and a high-frequency impact response is often induced when the roller hits the trailing edge of the spall. The conventional spall size estimation methods thus attempt to capture these events (entry, impact, and exit) and use their time difference to estimate the spall size. But the limitation of these methods is that they were mostly built on artificial spalls and have proved scarcely effective in dealing with natural ones. A recent study investigated the effect of these events on bearing stiffness and reported that the stiffness of the bearing structure decreases when the rolling element traverses the spall zone. Inspired by the study, a novel approach is proposed in this paper, which utilises the duration of natural frequency perturbations (induced by stiffness variation) of the bearing structure to perform spall-size estimation. Compared to the existing methods, this approach investigates the instantaneous resonance frequency variation during the spall span instead of the signal events at the entry and exit points. This novel approach along with three other representative existing methods are tested on three experimental datasets: one obtained by an artificially induced spall and the other two by naturally extended spalls. The performance analysis results reveal that all the methods are effective for artificial spalls, but only the proposed approach is effective for naturally extended spalls.